2005
DOI: 10.1360/04yc0048
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of photosynthesis in two new chlorophyll b-less rice mutants

Abstract: Leaves of the two new chlorophyll b-less rice mutants VG28-1, VG30-5 and the wild type rice cv. Zhonghua 11 were subjected to temperatures 28, 36, 40, 44 and 48 degrees C in the dark for 30 min or gradually elevated temperature from 30 degrees C to 80 degrees C at 0.5 degrees C/min. The thermostability of photosynthetic apparatus was estimated by the changes in chlorophyll fluorescence parameters, photosynthetic rate and pigment content, chloroplast ultrastructure and tissue location of H2O2 accumulation. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
2
21
1
Order By: Relevance
“…5) indicated that chloroplast ultrastructure of rice Chl b-less mutants was not altered as much in our planting conditions as it was in the barley Chl b-less mutant. The normal chloroplast ultrastructure, with intact envelope and grana stacking in rice Chl b-less mutants, was also seen when the leaves were given a 35 ºC treatment for 30 min in the dark (Lin et al 2005). Therefore, our results in this context differ from the reports of Staehelin (1986) or Rozak et al (2002).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…5) indicated that chloroplast ultrastructure of rice Chl b-less mutants was not altered as much in our planting conditions as it was in the barley Chl b-less mutant. The normal chloroplast ultrastructure, with intact envelope and grana stacking in rice Chl b-less mutants, was also seen when the leaves were given a 35 ºC treatment for 30 min in the dark (Lin et al 2005). Therefore, our results in this context differ from the reports of Staehelin (1986) or Rozak et al (2002).…”
Section: Discussioncontrasting
confidence: 85%
“…The LHC apoproteins need Chl b for stable integration (Preiss and Thornber 1995). An evidenced modulation of Chl-protein complexes and the ratio of excited energy distribution between two photosystems have been observed in two Chl b-less mutants in our previous work (Lin et al 2003b). Hence, the sensitivity of chloroplast ultrastructure to photooxidation stress in these mutants in particular grown under HI is reasonably ascribed to the instability of chloroplast structure and function in the absence of Chl b.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…2E). This agrees with the results obtained for other high-yielding rice mutants (Dai et al 2003, Lin et al 2003a.…”
Section: --supporting
confidence: 92%